Thermal–Mechanical Processing and Strengthen in AlxCoCrFeNi High-Entropy Alloys - Li, Jinshan; Yang, Haoxue; Wang, William Yi; Kou, Hongchao; Wang, Jun (Frontiers in Materials, 2021)
High-entropy alloys (HEAs) are devised based on a new alloy design concept which breaks the traditional designing methods for conventional alloys. As a novel alloy, HEAs have demonstrated attractive engineering properties, and possible combinations of diverse properties for their unique tunable microstructures and properties. This review article explains the phase transition mechanism and mechanical properties of high-entropy alloys under the thermal-mechanical coupling effect, which is conducive to deepening the role of deformation combines annealing on the structure control and performance improvement of high-entropy alloys, giving HEAs a series of outstanding performance and engineering application prospect. To reach this goal we have explored the microstructural evolution, formation of secondary phases at high and/or intermediate temperatures and their effect on mechanical properties in the famous AlxCoCrFeNi HEAs system, which not only has an important role in deepening the understanding of phase transition mechanism in AlxCoCrFeNi HEAs, but also has important engineering application value for promoting the application of high-entropy alloys.